Preparation and characterization of molybdenum oxide supported activated carbon for oxidative-extractive desulfurization / Izzaidah Riman - Riman, Izzaidah (2022)
Activated carbon derived from empty fruit bunch (AC-EFB) is seen as a potential catalyst to perform a desulfurization of fuel. However, due to its naturally small surface area and only relying on the activated carbon only, the desulfurization efficiency was not satisfying. Hence, surface modification and metal impregnation were subjected to the AC-EFB. This work aimed to investigate the performance of the potassium hydroxide (KOH) treated AC-EFB impregnated with molybdenum oxide (M0O3) as a catalyst to remove organosulfur compound dibenzothiophene (DBT) from the model diesel, isooctane at an optimised reaction condition. The carbonized EFB was treated with pore activator potassium hydroxide (KOH) and impregnated with series of concentration of M0O3 (5%, 10%, 15% and 20% wt%). The prepared catalysts were subjected to qualitative and quantitative characterizations such as thermal gravimetric analysis (TGA), X-ray diffraction (XRD), scanning electron microscopy (SEM), Brunauer-Emmett-Teller (BET) and X-ray fluorescence (XRF). The pore diameter of treated AC-EFB showed tremendous pore enlargement up to 4 ± 1 nm measured using Image J.